Akurasi Hasil Terjemahan Puisi Nizar Qabbani “Asyhadu An La Imraatan Illa Anti” Menggunakan Deepl Translator - Hasanah, Ummi; Aprilia, Lulu Eka; Fahmi, Muhammad; Hidayat, Rifki Maulana; Wirmansyah, Aulia Fadhila (Deskripsi Bahasa, 2025)
The rapid advancement of machine translation today is influenced by the progress in human intelligence. For instance, DeepL, as a translation machine, is considered highly accurate. The aim of this research was to analyze the accuracy of the translation of Nizar Qabbani's poem “Asyhadu An La Imra’atan Illa Anti” using Nababan's and Paul Ricoeur's theories. This study is qualitative in nature and employs a reading and note-taking method. Data analysis techniques followed Miles and Huberman's methods. Based on the research results, conclusions were drawn according to the research questions. Out of 18 datasets based on the 18 stanzas of Nizar Qabbani's poem “Asyhadu An La Imra’atan Illa Anti” translated using the AI-based DeepL Translator, 7 translations were categorized as low quality, 9 translations were categorized as less quality, and 2 translations were categorized as high quality. These results were obtained using Nababan's theory of translation accuracy. The translations produced by DeepL Translator for the poetry texts tended to be inconsistent, with many repeated words translated differently even in the same context. Further analysis using Paul Ricoeur's hermeneutic theory to examine the ideology within the text revealed that the translations tended to be very rigid for poetic texts.